2013
DOI: 10.1246/cl.130623
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically Highly Hydrophobic Semi-alicyclic Fluorinated Polyimide Aerogel with Ultralow Dielectric Constants

Abstract: Polyimide aerogel with an intrinsically hydrophobic nature and a dielectric constant as low as 1.19 at a frequency of 2.75 GHz was synthesized by the polycondensation of an alicyclic dianhydride, an aromatic fluorinated diamine, and an amino-substituted polyhedral oligomeric silsesquioxane (POSS) end-capper, followed by a supercritical carbon dioxide drying procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Relative k values as low as 1.16 at a frequency of X-band (~11-12 GHz) were obtained for PI aerogels made from 3,3′,4,4′-biphenyl tetracarboxylic dianhydride (BPDA), 2,2′-dimethylbenzidine (DMBZ), and 1,3,5-tris(4-aminophenoxy)benzene (TAB) crosslinker. Shen and coworkers have reported intrinsically highly-hydrophobic semi-alicyclic fluorinated PI aerogel with ultra-low k values of 1.17-1.19 in the frequency range of 2-12 GHz [25].…”
mentioning
confidence: 99%
“…Relative k values as low as 1.16 at a frequency of X-band (~11-12 GHz) were obtained for PI aerogels made from 3,3′,4,4′-biphenyl tetracarboxylic dianhydride (BPDA), 2,2′-dimethylbenzidine (DMBZ), and 1,3,5-tris(4-aminophenoxy)benzene (TAB) crosslinker. Shen and coworkers have reported intrinsically highly-hydrophobic semi-alicyclic fluorinated PI aerogel with ultra-low k values of 1.17-1.19 in the frequency range of 2-12 GHz [25].…”
mentioning
confidence: 99%
“…As a consequence, scCO2 is largely used in the production of nanoparticles, foams, aerogels, and membranes based on linear [85][86][87] or cross-linked [88][89][90][91][92] PIs. These materials have interesting features (high porosity, tunable shrinkage, nano-and micro-cavities, high surface area, ultralow dielectric constant, and mechanical resilience) that open up new possibilities in the applicability of PI-based systems such as catalytic systems, separation membranes, aviation, aerospace, construction, and others [93][94][95][96][97].…”
Section: Synthesis and Processing Of Pis In Supercritical Fluidsmentioning
confidence: 99%
“…Critical conditions are very different depending on the fluid which impregnates the wet gel, and the most commonly used is CO 2 [ 83 , 84 ]. For example, PI aerogels with an intrinsically hydrophobic nature and a dielectric constant as low as 1.19 were prepared by a supercritical CO 2 drying procedure [ 85 ]. Kobayashi et al [ 86 ] reported a structurally new type of aerogel with a 3D ordered nanofiber skeleton of liquid-crystalline nanocellulose by supercritical CO 2 drying.…”
Section: Preparation Of Polymer/carbon Aerogelsmentioning
confidence: 99%
“…Polyimides are widely used in industries for their high performance, such as ultralow dielectric constant, high mechanical strength and thermal stability at high temperatures [ 16 , 85 , 99 , 141 , 142 , 143 , 144 , 145 ]. Therefore, it would be ideal to design PI aerogels for use as highly porous, lightweight and high-temperature stable materials.…”
Section: Structures and Properties Of Polymer/carbon-based Aerogelmentioning
confidence: 99%